Using the Theory of Planned Behavior to Understand Factors Influencing South Asian Consumers' Intention to Seek Pharmacist-Provided Medication Therapy Management Services - Shaquib Al Hasan; Jagannath Mohan Muzumdar; Rajesh Nayak; Wenchen Kenneth Wu (MDPI AG, 2019)
The study purpose was to use the theory of planned behavior to understand factors influencing South Asian consumers’ intention to seek pharmacist-provided medication therapy management services (MTMS). Specific objectives were to assess effects of attitude, subjective norm (SN), perceived behavioral control (PBC), and socio-demographics on South Asian consumers’ intention to seek MTMS. Participants who were ≥18 years of age, of South Asian origin, with a previous visit to a pharmacy in the US for a health-related reason, and with ability to read and comprehend English were recruited from independent pharmacies in New York City. Responses were obtained through a self-administered survey. Descriptive statistics were performed, and multiple linear regression analysis was conducted to assess the study objective. SPSS was used for data analyses. Out of 140 responses, 133 were usable. Mean scores (standard deviation) were 4.04 (0.97) for attitude, 3.77 (0.91) for SN, 3.75 (0.93) for PBC, and 3.96 (0.94) for intention. The model explains 80.8% of variance and is a significant predictor of intention, F (14,118) = 35.488, p < 0.05. While attitude (β = 0.723, p < 0.05) and PBC (β = 0.148, p < 0.05) were significant predictors of intention, SN (β = 0.064, p = 0.395) was not. None of the socio-demographics were significant predictors of intention. Strategies to make South Asians seek MTMS should focus on creating positive attitudes and removing barriers in seeking MTMS.